Mixed Cryoglobulinaemic Glomerulonephritis Section Type II in the Setting of Rheumatoid Arthritis and Chronic Hepatitis B: A Case Report - Vijay Jeyachandran; Ram Pukar Bharat; Kapil Sejpal; Manish Balwani (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Mixed (Type II) cryoglobulinaemia is a systemic immune-complex vasculitis often linked to chronic infections especially Hepatitis C Virus (HCV) or autoimmune disease. Chronic Hepatitis B Virus (HBV) associated cryoglobulinaemic is rare, and its coexistence with Rheumatoid Arthritis (RA) is especially unusual. The authors report a 45-year-old female with long-standing seropositive RA on methotrexate and chronic HBV presented with fatigue, arthralgias, palpable purpura on her legs, and new-onset oedema. Laboratory workup showed elevated serum creatinine, nephrotic-range proteinuria, hypoalbuminaemia, haematuria, and a positive Rheumatoid Factor (RF). Antinuclear Antibody (ANA) and Anti-double-stranded deoxyribonucleic acid (anti-dsDNA) were negative. Complement levels i.e., Component 3 (C3) moderately reduced, Component 4 (C4) severely low, and positive mixed cryoglobulins with a high Immunoglobulin M (IgM) cryocrit. HCV and Human Immunodeficiency Virus (HIV) serologies were negative. Renal biopsy showed a diffuse endocapillary proliferative, Membranoproliferative Glomerulonephritis (MPGN) with hyaline “pseudothrombi.” Immunofluorescence disclosed granular capillary wall deposits of IgM, Immunoglobulin G (IgG) (both kappa and lambda), C3, and C1q, consistent with Type II cryoglobulinaemic GN. Treatment included high-dose corticosteroids and HBV antiviral drugs. Despite antiviral therapy and plasmapheresis, renal failure progressed requiring haemodialysis, and the patient died within three weeks due to disease-related complications and nosocomial infection. The present case highlights that RA and HBV can together underlie cryoglobulinaemic GN. Early recognition using RF, complement, and cryocrit testing and biopsy-guided therapy are critical. Purpura, positive RF, and low C4/C3 should prompt consideration of mixed cryoglobulinaemic vasculitis.